Assessment of the Role of the Mandibular First Molar Tooth in Mandibular Fracture Patterns of 29 Dogs. (March 2019) - Scherer, Ellen; Hetzel, Scott; Snyder, Christopher J.
Mandibular fractures at the level of the first molar tooth (M1) were assessed in 29 dogs. Patients included in this study demonstrated fractures involving the M1 tooth, tooth bud, or alveolus (if tooth was absent). Diagnostic imaging evaluation included intraoral dental radiography and/or computed tomography (CT) with 3D reconstruction. The distal root was involved in 55.2% of cases, mesial root involvement in 34.5% of cases, and the tooth was absent in 10.3% of cases. Fractures were described in the rostral-to-caudal direction. Fractures tended to occur in the caudoventral direction ( P = .057). Cases with CT imaging were also evaluated in the buccolingual direction. Fractures were found to occur significantly more frequently in the caudolingual direction ( P = .022). When classifying fracture patterns along M1 according to a previously published fracture classification system, it was noted that fractures occurred significantly more frequently in either the mesial ( P < .001) or distal ( P < .001) roots by coursing along the periodontal ligament space and communicating with the periapical region. Active or nonworsening periodontitis was described as radiographic or tomographic evidence of (>25%) bone loss in the vertical or horizontal direction. Periodontitis was associated with 7 (24.1%) cases. These results help frame the challenges associated with fracture repair at the M1 location. Treatment planning considerations should include limited structural support caudal to fractures involving the distal root, more frequent involvement of the distal root over the mesial root, risk for poor endodontic prognosis, and the predilection for unfavorable fracture patterns to occur.